God images, ethical effects and the responsibility of systematic theology - R. Venter (Acta Theologica)
This article registers an important shift that is occurring in contemporary theistic reflection: greater sensitivity to the function of God images, and the consequent ethical impacts. Three texts by Gunton, Johnson and McFague are discussed that exemplify this focus in an emphatic way. From this treatment the implications for Systematic Theology crystallise clearly. The rest of the article entails an exploration of the dynamics of the causal relationship between a specific God image and its corresponding effect. The ramifications for the task and responsibility of Systematic Theology are identified and in conclusion some normative guidelines are suggested.